?MEASUREMENT OF SULPHUR DIOXIDE AND PMIO AT KORANGI INDUSTRIAL AREA AND PHOTOCHEMICAL OXIDANTS AT UPTOWN AREA OF KARAcm (Biological Sciences - PJSIR, 2000)
Baseline measurements of sulphure dioxide and PMI 0 were carried out by Air Pollution Monitoring Mobile Laboratory in the Korangi Industrial Area of Karachi. This is the first study performed in this area. The highest concentration of SO2 and PMIO was found to be 25.8 and 177.9 Ilgm-3respectively. Both S02 and PMIO shows similar variations throughout the measurement period, this indicates that these pollutants originate from a similar source. Traffic density at the sampling site was also low and it was concluded that the contribution of SO2and PMI0 from mobile sources in this area is relatively small. The pollution found in this area is mostly within WHO threshold limits. Ozone and oxides of nitrogen were also measured at a sampling site located in the uptown area of Karachi. Average variations ofO 3'NO, NO" and solar radiation have been presented for winter. The formation of ozone due to photochemical reactions has also been discussed. Ambient concentrations of NO, NO, and 03' are strongly interrelated. It has been concluded that the level of photochemical oxi- dants found in this area during winter time is mainly due to vehicular traffic from near by super high way.